A method combining a kit with the Bionic e-Eye for rapid on site detection of diarrhetic shellfish poisoning. Issue 22 (23rd May 2018) - Qiu, Xianxin; Zhong, Longjie; Gan, Ying; Su, Kaiqi; Hu, Shihui; Wang, Ping
Abstract : A method combining a kit with the Bionic e-Eye for rapid and portable on site detection of diarrhetic shellfish poisoning. Abstract : Okadaic acid is a kind of fat-soluble diarrhetic shellfish poison existing extensively in shellfish. The rapid on site detection of shellfish contaminated by the toxin is a serious problem. Herein, a new method combining a kit with the Bionic e-Eye was developed for the rapid detection of okadaic acid on site. After optimization the kit reached a very low limit of detection, 0.19 μg L −1, and the linear detection range was 0.2–10 μg L −1 . The cross reaction rate with dinophysistoxins 1 was 23.6%. The kit had a small cross reaction with other kinds of toxin like saxitoxin, gynotoxin 2 & 3 and pectenotoxins 2-b. The recovery range was about 75.78–102.56%, and the CVs were lower than 20%. A correlation analysis was conducted between the Bionic e-Eye and a microplate reader in PBS and shellfish backgrounds. The detection results of the real shellfish samples by the Bionic e-Eye exhibited great consistency with high performance liquid chromatography. The total time taken to perform the detection was less than 90 minutes. Above all, the method integrated kit with the Bionic e-Eye was very suitable for the rapid detection of okadaic acid on site.